2017
DOI: 10.1002/cne.24368
|View full text |Cite
|
Sign up to set email alerts
|

GABAA and GABAB receptor subunit localization on neurochemically identified neurons of the human subthalamic nucleus

Abstract: The subthalamic nucleus (STN) is a critical excitatory signaling center within the basal ganglia circuitry. The activity of subthalamic neurons is tightly controlled by upstream inhibitory signaling centers in the basal ganglia. In this study, we used immunohistochemical techniques to firstly, visualize and quantify the STN neurochemical organization based on neuronal markers including parvalbumin (PV), calretinin (CR), SMI-32, and GAD . Secondly, we characterized the detailed regional, cellular and subcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 123 publications
(171 reference statements)
4
14
1
Order By: Relevance
“…Notably, quantitative analysis of the topographic distribution of Pvalb + neurons indicated that glutamatergic PV+ neurons were particularly prevalent in the dorsolateral and middle STN ( Figure 4C, D ). Our serial multiplex-smFISH data provide direct evidence that PV+ STN cells are glutamatergic with topographic segregation in the STN (Hontanilla et al, 1998; Wu et al, 2018) and suggest that parvalbumin cannot reliably serve as a marker for GABAergic interneurons, together with previous findings (Jinno and Kosaka, 2004; Shang et al, 2015; Wallace et al, 2017).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Notably, quantitative analysis of the topographic distribution of Pvalb + neurons indicated that glutamatergic PV+ neurons were particularly prevalent in the dorsolateral and middle STN ( Figure 4C, D ). Our serial multiplex-smFISH data provide direct evidence that PV+ STN cells are glutamatergic with topographic segregation in the STN (Hontanilla et al, 1998; Wu et al, 2018) and suggest that parvalbumin cannot reliably serve as a marker for GABAergic interneurons, together with previous findings (Jinno and Kosaka, 2004; Shang et al, 2015; Wallace et al, 2017).…”
Section: Resultssupporting
confidence: 52%
“…Thus, our serial smFISH, immunostaining, and topographic analysis confirmed that most neurons in the STN are purely glutamatergic. Previous anatomical studies have reported the presence of parvalbumin-expressing (PV+) neurons in the STN (Alkemade et al, 2019; Hontanilla et al, 1998; Lévesque and Parent, 2005; Wu et al, 2018). PV expression is conventionally interpreted to reflect a GABAergic subpopulation (Hu et al, 2014), which is inconsistent with our serial smFISH results and previous studies (Lévesque and Parent, 2005; Roccaro-Waldmeyer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA B receptors are mainly located in the presynaptic and postsynaptic regions of synapses in the hippocampus, thalamus, and cerebellum. [ 14 , 15 ] Mice lacking GABA B receptors develop epilepsy and deficits in memory, learning, and behavior. [ 2 6 ] Qiao et al [ 2 ] and Cui et al [ 4 ] have reported that, in China, patients with anti-GABA B receptor encephalitis are mainly male and have a median age at presentation of 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no direct data supporting this later hypothesis, it is possible that there is differential localization of various presynaptic receptors on Vglut2+ terminals within the SNpc versus SNpr that could variably regulate the release of glutamate. It has been reported that there are various presynaptic receptors located on STN terminals, such as the cannabinoid (Sánchez‐Zavaleta et al., 2018) and GABA (Wu, Song, Faull, & Waldvogel, 2018), making it possible that these receptors are differentially distributed within various neurons of the STN.…”
Section: Discussionmentioning
confidence: 99%